Single-Biocatalyst Synthesis of Enantiopure d-Arylalanines Exploiting an Engineered d-Amino Acid Dehydrogenase - Parmeggiani, Fabio; Ahmed, Syed T.; Thompson, Matthew P.; Weise, Nicholas J.; Galman, James L.; Gahloth, Deepankar; Dunstan, Mark S.; Leys, David; Turner, Nicholas J. (Advanced synthesis & catalysis, 2016)
A practical and efficient biocatalytic synthesis of aromatic d‐amino acids has been developed, based on the reductive amination of the corresponding α‐keto acids via a recombinant whole cell system composed of an engineered dehydrogenase and cofactor recycling apparatus. The reaction was shown to give excellent enantioselectivity (≥98%) and good yields at the preparative scale across a broad range of substrates. Additionally, the structure of the variant enzyme was solved to allow rationalisation of the observed reaction rates. The engineered whole cell catalyst was also used to mediate the production of d‐phenylalanine derivatives from racemic mixtures and cheaper l‐amino acids by combining it with an enantiocomplementary deaminase.